I soffitti lignei dipinti del XIV e XV secolo nel mezzanino di Palazzo Vecchio: storia di un recupero - Pini, Serena (Opus Incertum, 2018)
There are still some loose ends regarding the history of the construction and subsequent transformation of Palazzo Vecchio. This paper presents new information concerning one of the lesser-known floors of the building, the so-called Mezzanino, as a result of a series of unpublished considerations regarding the restoration work carried out by Alfredo Lensi between 1929 and 1932. It briefly retraces the history of the floor and the hypotheses concerning the modifications that may have been carried out by Michelozzo di Bartolomeo, as well as its various intended usages. The paper then describes 20th century interventions, focusing on the discovery and restoration of three painted platforms and the friezes and cornices below them which are now visible in the Mezzanino:  the first two, in the Terrazzino and Marzocco rooms, have almost identical 14th century decorations, whereas the third, which dates back to the late 15th century, is located in the Gigli d’oro Hall. The documents and photographs related to the project show how the three ceilings and their respective decorations are original, although they were retouched during the restoration works. They also prove that the 15th century platform was transferred to the Gigli d'oro from the Marzocco, where it covered an earlier 14th century ceiling.